Parasocial romantic relationships, romantic beliefs, and relationship outcomes in U.S. adolescents: rehearsing love or setting oneself up to fail?. Issue 3 (3rd July 2018) - Tukachinsky, Riva; Dorros, Sybilla M.
Abstract: The study examines the associations between adolescents' emotional and physical aspects of parasocial romantic relationships with media figures, idealized romantic beliefs, perceptions of a current dating partner, and relationship satisfaction. A two-study design included concurrent data from 153 adolescents ages 13–17 (55.6% female), and retrospective data from 274 college students ages 18–22 (79.8% female). Across both samples, emotional involvement in a PSRR was related to more idealized romantic beliefs. The intensity of emotional involvement with the media figure during adolescence was associated with lower relationship satisfaction and less favorable perceptions of a current romantic partner in college students. However, there were no significant associations between physical attraction to the media figure and relationship outcomes.